Assessing Niemann-Pick Type C (NP-C) through a multi-omics approach genomic and transcriptomic profile of challenging cases - Encarnação, Marisa (2020)
Niemann-Pick type C (NP-C) is a neurodegenerative Inherited Metabolic Disease with a heterogeneous clinical presentation, due to mutations in either the NPC1 or NPC2 genes. We studied patients with clinical diagnosis of NP-C but presenting inconclusive results regarding biomarkers testing and molecular analysis. Using NGS- targeted DNA sequencing we have identified some novel putative mutations and subsequent cDNA analysis allowed us to stablish the functional effect of a silent mutation (previously reported as a polymorphism) in the NPC1 splicing process. We demonstrated that this mutation leads to exon skipping, frameshift and premature stop codon and identified it in two NP-C patients from two unrelated Portuguese families. This mutation most likelly leads to a very unstable transcript that was overlooked. Also, to better characterize the pathomechanisms related to specific disease-causing mutations in NP-C patients, we analysed gene expression profiles in cultured skin fibroblasts and compared them to control individuals using Massively Parallel RNA Single-Cell Sequencing (MARS-Seq). The most prominent hits from this transcriptomics analysis were validated by qRT-PCR. The MARS-Seq analysis showed that a number of genes were upregulated and a significant number of the highly enriched genes are related to the unfold protein response (UPR) and Endoplasmic Reticulum (ER) stress, in a specific patient, which deserves further studies. ER stress is a hallmark of many neurodegenerative diseases, including LSD and can be due to misfolded/unfolded proteins as result of a specific missense mutation. Our preliminary results suggest that UPR activation is variable among NP-C patients, and this is likely to depend on the mutation type. Several other factors may contribute to this though, which could explain the heterogeneous presentation of this pathology. Additionally, we have investigated the same patients studied in MARS-Seq at the protein and celular levels. Interestingly, and according to recently published work, we observed that, for the analyzed mutations a significant part of the mutated NPC1 protein was retained/ delayed in the ER.